1968
DOI: 10.1139/f68-025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stage of Rigor and of Freezing–Thawing Processes On Storage Quality of Refrozen Cod

Abstract: frawler-caught cod were frozen before and after rigor mortis in brine (23l, NaCl) and between refrigerated plates, thawed in circulating water at 7 C or in a conveyorized microwave oven, then processed into fillets which rvere packaged, plate-frozen, and stored at -18 C.All samples thawed satisfactorily in circulating water. Some overheating was encountered during thawing in microwaves. But the equipment was not developed sufficiently to permit assessment of the commercial potential of microwave thalving.Exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Peters et al (1968) found that freezing pre-rigor was preferable to freezing postrigor with respect to the sensory properties while Love (1988; showed that the degree of gaping was least in thawed marine species when the fish had been frozen pre-rigor.…”
Section: Introductionmentioning
confidence: 99%
“…Peters et al (1968) found that freezing pre-rigor was preferable to freezing postrigor with respect to the sensory properties while Love (1988; showed that the degree of gaping was least in thawed marine species when the fish had been frozen pre-rigor.…”
Section: Introductionmentioning
confidence: 99%
“…Dyer et al (1962) reported accelerated deterioration for refrozen cod (Gadus morhua) fillets stored at Ϫ23ЊC but confounded any effects of thawing and refreezing with product form by using whole fish as once frozen controls. Peters et al (1968) compared refrozen fillets with once frozen fillets from the same batch but reported slight (sometimes non-significant) taste panel differences after 12 months at Ϫ18ЊC. The use of composite sensory attribute measurements, such as 'overall taste panel score' or 'overall taste/texture score', has also been common (Dyer et al, 1962;Peters et al, 1968) preventing evaluation of effects that thawing and refreezing might have on specific sensory attributes.…”
Section: Introductionmentioning
confidence: 99%
“…This binding occurs through the coupling of actin and myosin by consuming adenosine triphosphate as energy and results in the loss of muscle extension ( Yao et al, 2019 ). Peters et al (1968) found that freezing fish pre-rigour produced a higher quality product than freezing in- or post-rigour. However, Hedges (2002) noted that if thawing occurs before rigour is complete, the fish may complete rigour during the thawing process, which will result in excessive drip loss and damage to the flesh.…”
Section: Survey Methodsmentioning
confidence: 96%